EIB Group Sustainability Report 2021 - European Investment Bank (2022)
"Over the last years, the European Investment Bank Group has shown that fighting COVID-19, financing the recovery, and investing in climate action and environmental sustainability are mutually supportive goals. Innovation, development and green finance are the cornerstones of our approach to creating a more sustainable economy. In 2021, the coronavirus pandemic continued to disrupt lives and businesses around the globe. At the same time, it became clear that the climate and environment crises had reached emergency levels. Urgent action is required if we are to meet the Paris Agreement's commitments and avoid biodiversity loss. The European investment Bank Group is ready to tackle these challenges, the biggest of our time. This report shows how we delivered a record €94.9 billion in financing in 2021, supporting sustainable and inclusive growth in Europe and beyond. The Sustainability report should be read in conjunction with its two annexes, the GRI and SASB disclosures, as well as with the Group's 2021 TCFD report."